PENGARUH PENERAPAN SISTEM AKUNTANSI KEUANGAN DAERAH TERHADAP KELAYAKAN PELAPORAN PERTANGGUNGJAWABAN KEUANGAN PADA BADAN KEPEGAWAIAN DAERAH KABUPATEN POHUWATO - Syamsuddin Syamsuddin (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2018)
The purpose of this study is (1) to measure the influences of application the Regional Financial Accounting System which consists of a recording system and an accounting basis for the feasibility of reporting financial accountability at the Pohuwato Regional Civil Service Agency. (2) To discover influence effect of applying the recording system to the feasibility of financial accountability reporting at the Pohuwato Regional Civil Service Agency partially. (3) To find outinfluence effects of application accounting bases on the feasibility of reporting financial accountability at the Pohuwato Regional Civil Service Agency. The results of this study indicate that the recording system sub-variable is the dominant determinant of the feasibility of reporting financial accountability, which imply that a preferable recording system is refers to the basic accounting equation, the financial reporting feasibility of accountability is more appropriate. Furthermore, it is also influenced by transactions that occur in general, always recording, classifying and summarizing. Partial or individual (X2) accounting basis have a positive effect on the feasibility of reporting financial liability of 0.0485 or 4.85%.This is due to the fact that in the basis of accounting applied two systems, namely cash basis and accrual basis, therefor that financial report makers are occasionally inconsistent in the application of the two systems. Thus to produce the feasibility of reporting financial accountability more properly, it needs to be done perfection in the accounting base sub-variable.